DANDA NATA OF ODISHA: A CRITICAL ANALYSIS OF ITS CULTURAL AND RITUALISTIC DIMENSIONS WITH SPECIAL REFERENCE TO BOUDH - Tripathy, Dibya Ranjan; Mallik, Santosh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Danda Nata is a vibrant folk tradition celebrated in rural and tribal communities of Odisha, with Boudh district standing out for its unique variations. Held annually during Chaitra (March–April), the festival spans thirteen or twenty-one days and culminates on Maha Vishuba Sankranti. The celebration is marked by rhythmic drumming, energetic dance, dramatic acts, and comedic performances, blending spiritual rituals with theatrical expressions. Central to the festival are the devotees, known as Danduas or Bhoktas, who undertake vows of austerity and devotion, guided by the Pata Dandua or Pata Bhokta. The event unfolds in four phases: Dhuli Danda, Pani Danda, Agni Danda, and Suanga Danda. Each phase involves distinct rituals, physical endurance, and purification through sand, water, and fire. The final phase, Nrutya Danda, features dance, music, and satire. Boudh’s Danda Nata is distinct for incorporating Bandana, a devotional recitation, Dalapuja, a special puja performed before Meru, and Sola Suanga Danda Nata, which includes sixteen forms of dramatic and satirical performances. These elements add depth to the festival, blending humor, folklore, and religious themes. The worship of Lord Shiva and Goddess Kali ties Danda Nata to both Hindu and indigenous traditions. The performance, accompanied by instruments like the dhol, mahuri, flute, and mardal, remains a dynamic cultural experience. In Boudh, Danda Nata continues to evolve, preserving its spiritual and artistic heritage, making it a unique and living expression of Odisha’s folk traditions.